Effectiveness of a Culturally Integrated Liver Cancer Education in Improving HBV Knowledge Among Asian Americans - Juon, Hee-Soon (2012)
OBJECTIVE: To assess the effectiveness of a hepatitis B virus (HBV) educational program in increasing HBV knowledge. METHODS: Using a cluster randomized control trial to recruit participants from the community-based organization in the Baltimore-Washington Metropolitan Area; a total of 877 Asian American participants completed a self-administered pretest. HBV knowledge was the outcome measure. The intervention group received a 30-minute educational program. After the educational program, the intervention group completed post-education survey. Six months after the education, all participants were followed by phone. RESULTS: The intervention group showed significantly higher knowledge scores than the control group at the 6-months follow-up (between-group difference was 1.44 for knowledge of transmission modes and 0.59 for sequelae, p < 0.01). For the intervention group, the increase in knowledge of HBV transmission modes in post-education was much higher than that at the 6-month follow-up (4.18 vs. 2.07), p < 0.01) compared to baseline. Age was also an important factor on the educational effect: Those older than 60 years reported the lowest scores in all three points. CONCLUSIONS: Findings suggest that this culturally integrated liver cancer educational program increased HBV knowledge. Differential strategies are needed to target age groups, separately educating those younger and those older.